Efektivitas Pemanfaatan Limbah Tahu Cair Melalui Metode Frekuensi Waktu Penyiraman terhadap Pertumbuhan Produksi Rumput Gajah (Pennisetum purpureum) - Maria M. M. Mau; Oktovianus R. Nahak T. B.; Kristoforus W. Kia (JAS, 2020)
This research was conducted in the experimental garden of the Faculty of Agriculture, University of Timor, Sasi, North Central Timor Regency. The research will last for 1 production period (45 HST), from the end of March to the beginning of June 2019. The purpose of this study is to analyze the value of growth and production of Pennisetum purpureum treated with frequency of time watering liquid tofu waste. This research is an experimental study using a randomized design Complete (CRD) consisting of 4 treatments and 4 replications so that there are 16 units of the experimental unit. The treatments tested consisted of: R0 = Without watering tofu waste, R1 = Frequency of watering once every 2 days, R2 = Frequency of watering once every 4 days, R3 = Frequency of watering once every 6 days. The variables observed in this study were plant height, stem diameter, leaf fresh weight and leaf dry weight. The results showed that giving treatment of the frequency of time of watering the liquid tofu waste, had a significant effect on the fresh weight of leaves produced but did not differ on plant height of stem diameter and dry weight produced. It could be concluded that liquid tofu waste with good watering time frequency was found in the treatment R1 which is 2 days, liquid tofu waste has the ability to improve soil texture and can stimulate the growth of Pennisetum purpureum in this case the growth of plant height, stem diameter, leaf fresh weight, and leaf dry weight.